Pengaruh Profitabilitas, Likuiditas, Dan Solvabilitas Terhadap Harga Saham Perbankan Dengan Inflasi Sebagai Variabel Moderating Pada Periode 2007-2015 - Nyi Mas Rizki Noviyah (Jurnal Manajemen dan Bisnis Indonesia, 2018)
The purpose of this study is to analyze the effect of profitability (ROA), liquidity (LDR), and solvency (DER) to the stock price of banking and find out whether inflation moderates the effect of profitability (ROA), liquidity (LDR), and solvency (DER) to the stock price of banking. Data collection method used is the method of research libraries. Data analysis technique used is multiple linear panel regression and hypothesis testing using t-statistics as well as the interaction test Moderated Regression Analysis (MRA) with significance level of 5 percent. Data were processed using Eviews program ver. 6.0. The results showed that the profitability (ROA) and liquidity (LDR) have positive and significant impact to the stock price of banking, but the solvency (DER) have negative and significant impact to the stock price of banking.. In addition, inflation is moderating influence liquidity (LDR) and solvency (DER) to the stock price of banking. While on influence profitability (ROA) to the stock price banking, inflation does not moderate significantly. Keywords: profitability (ROA), liquidity (LDR), solvency (DER),stock price of banking, inflation